Foreign aid and sustainable forestry - Pekka E. Kauppi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Foreign aid can contribute to sustainable forestry in many ways. The goal is to secure forest benefits of the future, without compromising the needs of the present generations. This paper elaborates on forestry aid as it has evolved in the past. Future directions are suggested, referring to short and midterm projects, as well as long-term programmes. Tree planting has worked in the past, and is an option for scaling up the activity in the future. Distributing fuel efficient cooking stoves could work in a similar way, sparing trees and at the same time improving the quality of rural life. Planted trees and new stoves can be made available in the near term, that is, within a time horizon of one to five years. In the mid-term, over a time span of 5-15 years, forest inventory and monitoring systems are relevant candidates for successful foreign aid in forestry, although the methods are not yet sufficiently developed to become applied in tropical rain forests. The support of universities and the infrastructure for higher education in forestry, agriculture, and rural development, is important in the long term. Forestry, which generally operates in remote rural areas, is susceptible to logistical problems and resource misuse. It is important in forestry aid to circumvent corruption risks of both in recipient nations and in donor organizations. Forestry aid must emphasize domestic action by local experts, as well as capacity building in the recipient countries.
Keywords: Q0; Q01; 330; forestry aid; sustainable forestry; development; forestry paradigms